Evaluation of Arch Width Variations Among Different Skeletal Patterns in Chhattisgarh Population - Dr. Sham Susar; Dr. Pradeep Babu Kommi; Dr. Shirish Goel; Dr. Tanuj Choudhari; Dr. Mukul Maldhure; Dr. Srushti Shinde (The Bioscan, 2025)
Aim: To evaluate the arch width variations among different skeletal patterns in Chhattisgarh population. Materials and Methods: A total of 66 untreated adults (33 males and 33 females), the age of 15-30, with minimal crowding or spacing and no cross bites, were included in the study. Lateral cephalograms were analyzed to measure the angle between the anterior cranial base and the mandibular plane (MP-SN). Dental casts were used to record maxillary and mandibular inter-canine, inter-premolar, and inter-molar widths. Results: Findings revealed that males had significantly wider dental arches than females (P < 0.05). Additionally, as the MP-SN angle increased, there was a notable reduction in arch width. When compared with data from other populations, the results also suggested that arch width dimensions vary across different ethnic and racial groups. Conclusion: Dental arch width is affected by gender, ethnicity, and vertical facial structure. Hence, orthodontic treatment should consider using customized arch wires tailored to the individual’s original arch form and width.